PENERAPAN PENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY (SETS) BERBANTUAN MACROMEDIA FLASH DILENGKAPI ARTIKEL ILMIAH TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA MATERI PERUBAHAN FISIKA DAN KIMIA - Nurcahyani A, Nunuk; Mahardiani, Lina; Mulyani, Bakti (Prodi Pendidikan Biologi FKIP UNS, 2012)
ABSTRAK The aim of this research is to know the influence of Science Environment Technology and Society (SETS) learning approach using macromedia flash completed with scientific articles toward the improvement of the student achievement on the subject matter of physical and chemical changes for seventh grade students SMP 14 Surakarta academic year of 2010/2011. This research used an experiment method using Randomize Control Group Pretest Postest Design. The population of this research was student of seventh grade of SMP 14 Surakarta in academic year 2010/2011. The sample consists of 2 classes, VII D as an experiment class (SETS learning approach using macromedia flash completed scientific articles) and VII E as the control class (conventional method) that obtained by cluster random sampling technique. The data of this research are collected by objective test to measure the cognitive achievement and questioner test to determine the affective achievement. Technique of analysis data used was t-test on the right. The result of this research showed that learning approach of SETS using macromedia flash completed scientific articles is more effective than conventional method toward the student achievement on the subject matter of Physical and Chemical Changes for seventh grade students even semester in SMP 14 Surakarta academic year of 2010/2011. It showed from the result of t-test that tobs > ttable are 3,63 > 1,67 for cognitive aspect achievement and 2,91 > 1,67 for affective aspect achievement. Furthermore, based on the average of cognitive achievement of the experiment class (21,611) was higher than control class (16.361). This result was also has the same value for affective achievement where for the experiment class (94,556) was higher than control class (88,111) Kata Kunci: SETS, Macromedia flash, scientific article, Physical and Chemical Changes.